Factors Affecting Disclosure of Internet Financial Reporting in The Government of The Bangka Belitung Islands - Yunita, Anggraeni; Wardhani, Rulyanti Susi; Hamsani, Hamsani (Future Science / FSH-PH Publications, 2022)
This study aims to examine the disclosure of regional financial statements in terms of political competition, government complexity and level of financial dependence. The research conducted is an empirical study. Empirical studies were conducted using secondary data obtained from observations. The research subjects are districts and cities in the province of the islands of Bangka Belitung, totaling 6 districts and 1 city. The object of research is the size, wealth, complexity, regional dependence and political competition on the disclosure of Internet Financial Reporting. The population of this study is all regencies and cities in the Province of the Bangka Belitung Islands from 2017 to 2020. The sample used in this study is a saturated sample where all members of the population are used as samples. The results show that the size of the local government does not affect the disclosure of internet financial reporting, the wealth of the local government has an effect on the disclosure of internet financial reporting, political competition has no effect on the disclosure of internet financial reporting and regional complexity has no effect on the disclosure of internet financial reporting.